RETRACTED: Mitofusin-2 Enhances Mitochondrial Contact With the Endoplasmic Reticulum and Promotes Diabetic Cardiomyopathy - Zhang, Jing; Zhang, Feng; Wang, Yanou (Frontiers in Physiology, 2021)
Diabetic cardiomyopathy has been associated with mitochondrial damage. Mitochondria–endoplasmic reticulum (ER) contact is an important determinant of mitochondrial function and ER homeostasis. We therefore investigated whether hyperglycemia can damage the mitochondria by increasing their contact with the ER in cardiomyocytes. We found that hyperglycemia induced mitochondria–ER contact in cardiomyocytes, as evidenced by the increased MMM1, MDM34, and BAP31 expressions. Interestingly, the silencing of Mfn2 reduced the cooperation between the mitochondria and the ER in cardiomyocytes. Mfn2 silencing improved cardiomyocyte viability and function under hyperglycemic conditions. Additionally, the silencing of Mfn2 markedly attenuated the release of calcium from the ER to the mitochondria, thereby preserving mitochondrial metabolism in cardiomyocytes under hyperglycemic conditions. Mfn2 silencing reduced mitochondrial reactive oxygen species production, which reduced mitochondria-dependent apoptosis in hyperglycemia-treated cardiomyocytes. Finally, Mfn2 silencing attenuated ER stress in cardiomyocytes subjected to high-glucose stress. These results demonstrate that Mfn2 promotes mitochondria–ER contact in hyperglycemia-treated cardiomyocytes. The silencing of Mfn2 sustained mitochondrial function, suppressed mitochondrial calcium overload, prevented mitochondrial apoptosis, and reduced ER stress, thereby enhancing cardiomyocyte survival under hyperglycemic conditions.